Jamstack Architecture as a Synthesis of Serverless Back-End and Dynamic Front-End - Vorobyov, M.; Sotnik, S. (NURE, 2026)
The paper examines JAMstack as an approach to building web applications, where static resources are delivered via a CDN, and business logic and integrations are handled through serverless functions and managed API services. It analyzes the typical JAMstack architecture, the role of the build process, ways to implement front-end dynamics, and the integration of headless CMS and databases. It shows how this model affects performance (TTFB, caching, server offloading), security (smaller attack surface, secret management, function isolation), and scalability (automatic scaling at the CDN and serverless levels). A comparison with traditional approaches is conducted, and practical recommendations for choosing JAMstack for different scenarios are formulated. У роботі розглянуто JAMstack як підхід до побудови вебзастосунків, у якому статичні ресурси віддаються через CDN, а бізнес-логіка та інтеграції виносяться у безсерверні функції та керовані API-сервіси. Проаналізовано типову архітектуру JAMstack, роль build процесу, способи реалізації динаміки у front-end та підключення headless CMS і баз даних. Показано, як така модель впливає на продуктивність (TTFB, кешування, розвантаження сервера), безпеку (менша площа атаки, керування секретами, ізоляція функцій) та масштабованість (автоматичне масштабування на рівні CDN і serverless). Проведено порівняння з традиційними підходами та сформульовано практичні рекомендації щодо вибору JAMstack для різних сценаріїв.
Архітектура Jamstack як синтез безсерверного Back-End та динамічного Front-End
Keywords: JAMstack; serverless; CDN; headless CMS